A kind of graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape and its preparation method and application

Through the preparation of anti-corrosion solvent-free precast composite tape of graphene modified coating, the harmful smoke and vapor problems generated by existing anti-corrosion coatings during welding and cutting are solved, and high-performance, solvent-free and environmentally friendly anti-corrosion effects are achieved, meeting the anti-corrosion needs of modern industries.

CN118950436BActive Publication Date: 2025-04-04SHENZHEN BEST ADVANCED MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411042134.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-04-04
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The zinc oxide smoke and zinc vapor generated during welding and cutting of existing anticorrosion coatings are harmful to human health, and the coating film is poor in density and low in strength, which cannot meet the high-performance demand of modern industry for anticorrosion materials.

Method used

By developing anti-corrosion solvent-free precast composite tape with graphene modified coating, it is uniformly sprayed and dried by mixing graphene oxide, ferric chloride and ferrous chloride. Then, the silane coupling agent is modified and the sol-gel reaction is reacted, combined with the treatment of anionic surfactant and hydrazine hydrate, a modified graphene composite sheet is formed, and mixed with epoxy resin and curing agent, and uniformly coated on the adhesive, to achieve the preparation of solvent-free precast composite tape.

Benefits of technology

It realizes the preparation of high-performance heavy anti-corrosion preforms, solves the problem of solvent volatilization and polluting the atmosphere. The product has the characteristics of simplicity of construction, high-performance anti-corrosion and anti-shock, and long service life, meeting the anti-corrosion needs of modern industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004972652820000141
    Figure BDA0004972652820000141
Patent Text Reader

Abstract

The present invention proposes a graphene-modified coating anti-corrosion solvent-free prefabricated composite adhesive tape and its preparation method and application, which belong to the field of anti-corrosion technology. Graphene oxide, ferric chloride and ferrous chloride are mixed evenly, spray-dried, and then modified by silane coupling agent KH560, sol-gel reaction, treated with anionic surfactant, reduced by hydrazine hydrate vapor, and mixed evenly with epoxy resin and curing agent to obtain graphene-modified coating, which is evenly coated on adhesive tape to obtain graphene-modified coating anti-corrosion solvent-free prefabricated composite adhesive tape. The present invention solves the problem of solvent volatilization polluting the atmosphere by developing new preparation technology, studying low surface treatment technology and developing an integrated coating process. Solvents are not used, and the construction is simple, high-performance anti-corrosion and anti-seepage products with long service life meet the anti-corrosion requirements of my country's rapidly developing industrial field, and have broad market prospects and important practical significance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion protection, and in particular to a graphene-modified coating corrosion-resistant solvent-free prefabricated composite adhesive tape, and a preparation method and application thereof. Background Art

[0002] In all fields of national economy and national defense construction, anti-corrosion technology is used in ships, bridges, oil platforms, buildings and even precision instruments. With the emergence of large-scale projects and equipment, people have more and more stringent requirements for anti-corrosion materials. They must not only have long-lasting anti-corrosion effects, but also meet the requirements of easy coating, easy curing, solvent-free and environmental protection. At present, all heavy anti-corrosion coatings are sprayed, which have a short service life, require high construction skills of workers, and have inconsistent quality. In addition, the solvents contained in the coatings will evaporate during the spraying process, pollute the environment, and workers will breathe them into their bodies, causing great harm to the body.

[0003] Zinc-rich primer is one of the most important and most commonly used heavy-duty anti-corrosion coatings for steel structures of ships, marine facilities, bridges, large equipment and various large buildings. Its anti-corrosion mechanism is based on the cathodic protection of metallic zinc powder on steel. The zinc powder content is closely related to its anti-corrosion effect, but the high content of zinc powder (60%-85%) also brings many disadvantages to zinc-rich primer: 1) The use of a large amount of zinc powder, the zinc oxide fume and zinc vapor generated during hot processing such as welding and cutting, will have an impact on human health and easily lead to "zinc fever"; 2) The high zinc powder content leads to poor density and low strength of the paint film, and poor matching with the topcoat; 3) The density of epoxy zinc-rich primer is about 3.0g / cm3, which is twice that of ordinary epoxy anti-rust primer, which does not meet the concept of weight reduction and consumption reduction of new ship coatings.

[0004] Graphene is widely used in the field of coatings due to its excellent properties such as large specific surface area and high electron mobility, which has also led to the rapid development of the coating field. Compared with traditional coatings, graphene-modified coatings have better performance and have been widely used in anti-corrosion coatings, conductive coatings, flame-retardant coatings, heat-dissipating coatings and other fields. In conductive coatings, compared with the metal conductive powder of traditional coatings, graphene has higher electron mobility and better conductivity; in flame-retardant coatings, graphene can use its dense structure to play a physical barrier role, and at high temperatures, due to the combustion of graphene, it produces flame-retardant CO2 gas, which plays a flame-retardant role; in heat-dissipating coatings, due to its high thermal conductivity and high specific surface area, it can increase the heat dissipation surface area of ​​the coating and improve the heat dissipation effect. There are three main methods for using graphene for corrosion protection. Among them, chemical deposition and electrochemical deposition have their own defects, while the graphene filler method is the simplest and most promising. It is also the most commonly used protection method on the market. However, this method has the following problems: First, the preparation technology has defects and cannot give full play to the excellent properties of graphene itself, but reduces the anti-corrosion effect. Secondly, there is a lack of research on surface treatment technology and dispersed coating process technology that matches solvent-free epoxy adhesive. Summary of the invention

[0005] The purpose of the present invention is to propose a graphene modified coating anti-corrosion solvent-free prefabricated composite tape and its preparation method and application. By developing new preparation technology, studying low surface treatment technology and developing an integrated coating process, the problem of solvent volatilization polluting the atmosphere is solved, and high-performance heavy-duty anti-corrosion prefabricated materials are prepared, which can be standardized prefabricated without the use of solvents, and have simple construction, high-performance anti-corrosion and anti-seepage, and long service life products, which meet the anti-corrosion requirements of my country's rapidly developing industrial field. The developed high-efficiency and environmentally friendly anti-corrosion solvent-free prefabricated composite tape has broad market prospects and important practical significance.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The invention provides a method for preparing a graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape. The method comprises the following steps: uniformly mixing graphene oxide, ferric chloride and ferrous chloride, spray drying, modifying the mixture with a silane coupling agent KH560, undergoing a sol-gel reaction, treating the mixture with an anionic surfactant, reducing the mixture with hydrazine hydrate vapor, uniformly mixing the mixture with an epoxy resin and a curing agent to obtain a graphene modified coating, and uniformly coating the coating on an adhesive tape to obtain the graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape.

[0008] As a further improvement of the present invention, the following steps are included:

[0009] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: adding ferric chloride and ferrous chloride to the graphene oxide aqueous dispersion under ice water bath conditions, stirring and mixing evenly, adjusting the pH value of the solution, spray drying, and solid ball milling to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0010] S2. Preparation of modified composite sheet: adding the wrinkled graphene oxide / Fe3O4 composite sheet to ethanol, adding silane coupling agent KH560, heating and stirring to react, filtering, washing, and drying to obtain a modified composite sheet;

[0011] S3. Sol-gel reaction: adding the modified composite sheet to water, adjusting the pH value of the solution, heating the reaction, filtering, washing, and drying to obtain a composite sheet;

[0012] S4 anionic surfactant treatment: the composite sheet was added to water, an anionic surfactant was added, the reaction was stirred, filtered, washed, and dried to obtain a treated composite sheet;

[0013] S5 reduction: the treated composite sheet is reduced by hydrazine hydrate vapor to obtain a reduced composite sheet;

[0014] S6. Preparation of graphene-modified coating: mixing the reduced composite sheet, epoxy resin and curing agent to obtain a graphene-modified coating;

[0015] S7. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: evenly apply the graphene-modified coating on the tape, heat and cure it, and obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0016] As a further improvement of the present invention, the concentration of the graphene oxide aqueous dispersion in step S1 is 0.5-1 mg / mL, the mass ratio of the graphene oxide aqueous dispersion, ferric chloride and ferrous chloride is 100:3.24:1.26, the pH value of the adjustment solution is 9-10, the conditions for the spray drying are an inlet air temperature of 95-120°C, an outlet air temperature of 30-50°C, an evaporated water amount of 2400-2700 mL / h, and the ball milling time is 1-3h.

[0017] As a further improvement of the present invention, the mass ratio of the wrinkled graphene oxide / Fe3O4 composite sheet and the silane coupling agent KH560 in step S2 is 10:1-2, the temperature of the heating and stirring reaction is 40-50°C, and the time is 2-3h; the pH value of the solution is adjusted to 10-11 in step S3, the temperature of the heating reaction is 60-70°C, and the time is 7-10h.

[0018] As a further improvement of the present invention, the mass ratio of the composite sheet and the anionic surfactant in step S4 is 12-15:2-4, and the anionic surfactant is selected from at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium tetradecyl sulfonate, sodium tetradecylbenzene sulfonate, sodium tetradecyl sulfate, sodium hexadecyl sulfonate, and sodium octadecyl sulfonate.

[0019] As a further improvement of the present invention, the reduction time in step S5 is 10-12 hours.

[0020] As a further improvement of the present invention, the mass ratio of the reduced composite sheet, epoxy resin and curing agent in step S6 is 2-4:100:15-20, the curing agent is selected from at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride and phthalic anhydride, and the epoxy resin is selected from at least one of E-51, E-44 and F-51.

[0021] As a further improvement of the present invention, the coating amount in step S7 is 300-400 g / m 2 The heating curing temperature is 50-60°C and the time is 2-4h.

[0022] The present invention further protects a graphene-modified coating anti-corrosion solvent-free prefabricated composite adhesive tape prepared by the above-mentioned preparation method.

[0023] The present invention further protects the use of the above-mentioned graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape in marine corrosion protection.

[0024] The present invention has the following beneficial effects:

[0025] The present invention solves the problem of solvent volatilization polluting the atmosphere by developing new preparation technology, studying low surface treatment technology and developing an integrated coating process, and prepares high-performance heavy-duty anti-corrosion prefabricated materials, which can be standardized prefabricated without using solvents, and have simple construction, high-performance anti-corrosion and anti-seepage, and long service life products, meeting the anti-corrosion requirements of my country's rapidly developing industrial field. The developed high-efficiency and environmentally friendly anti-corrosion solvent-free prefabricated composite tape has broad market prospects and important practical significance.

[0026] Graphene has unique electrical, chemical and structural properties, but its conjugated structure makes it less compatible with water, organic solvents and polymers, and it is prone to stacking and agglomeration, which affects its dispersibility and increases the difficulty of its application in the coatings field. The stacking and agglomeration of graphene sheets not only makes it impossible to achieve its excellent performance, but also deteriorates the performance of graphene-based marine coatings.

[0027] Through functional modification, the intrinsic properties of graphene can be retained, and the stability and dispersibility of graphene in the coating system can be improved. Not only can graphene be given richer physical, chemical, electrochemical and photoelectrochemical properties, but also the synergistic and synergistic effects between different functional materials can be brought into play. In addition, graphene's regular two-dimensional structure, large specific surface area, good conductivity, high structural strength, wide potential window, good modifiability and other characteristics make it an ideal carrier that can carry various organic and inorganic compounds, including ferrosoferric oxide and anionic surfactants.

[0028] Liquid bisphenol A epoxy resin (E-51, E-44) and bisphenol F epoxy resin (F-51) have low viscosity and small shrinkage during curing. The cured products have good adhesion, heat resistance, and chemical resistance. However, they have problems such as film brittleness and poor weather resistance, which affect their anti-corrosion properties after film formation.

[0029] Graphene oxide contains oxygen-containing functional groups such as hydroxyl (-OH), epoxy [-C(O)C-], carbonyl (-C=O), carboxyl (-COOH), ester (-COO-) etc. Therefore, graphene oxide can be used as a good carrier of inorganic substances. In order to solve the problem of brittle epoxy resin film, the present invention forms wrinkled graphene oxide loaded with Fe3O4 under alkaline instantaneous heating conditions by mixing graphene oxide with ferric chloride and ferrous chloride, spray drying, and then ball milling to form composite sheets. The wrinkled structure between graphene sheets can effectively reduce the stacking of graphene in the polymer matrix and avoid agglomeration caused by the ordered structure between graphene sheets, thereby being helpful to achieve uniform dispersion. The wrinkled graphene oxide composite sheet loaded with Fe3O4 can also improve the flexibility and wear resistance of the coating after hardening.

[0030] The obtained wrinkled graphene oxide / Fe3O4 composite sheet was further modified with silane coupling agent KH560 and then functionalized by sol-gel reaction to form a silane film, which further improved the corrosion protection and cathodic stripping resistance of the coating. Adding it to epoxy resin can also improve the weather resistance of the resin.

[0031] By adding suitable anionic surfactants, graphene oxide is non-covalently functionalized through ionic bond interactions, and the electrostatic attraction between the positive and negative charges of graphene and the modified molecules is used to stably disperse the system, further improving the dispersion stability of the product. Hydrazine hydrate is then used to reduce it to obtain modified graphene, which can be stably dispersed in water, and the surface of the reduced graphene oxide has a strong negative charge, which greatly improves the dispersibility and compatibility.

[0032] After the reduction composite sheet prepared by the present invention is modified, the hydrophobicity of a few layers of graphene (mainly 3-5 layers) is obvious, which plays a physical anti-corrosion role. The metal polymer composite coating is easy to break, and scratching the metal will accelerate the corrosion of the metal material at the damaged part. The graphene surface has low friction performance and has good wear resistance and corrosion resistance. Graphene reacts chemically with the active functional groups on the metal surface to form a good barrier layer, which plays an anti-corrosion role. Graphene can also prevent electrochemical corrosion at the same time. Metal materials lose electrons under the action of electrochemistry, and the graphene layers provide electrons with a good conductive effect. The electrons will be transferred to the metal coating. The cathode electrons will not occur directly on the metal, but will directly react with the coating, which will slow down the generation of iron hydroxide, prevent the metal material from losing electrons, and play a good anti-corrosion role. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a method for preparing a graphene-modified coating anti-corrosion solvent-free prefabricated composite adhesive tape, comprising the following steps:

[0036] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion under ice-water bath conditions, stirred and mixed for 15 min, the pH value of the solution was adjusted to 9, spray dried, and solid ball milled for 1 h to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0037] The spray drying conditions are as follows: the air inlet temperature is 100°C, the air outlet temperature is 30°C, and the evaporated water volume is 2400 mL / h;

[0038] S2. Preparation of modified composite sheet: 10 g of wrinkled graphene oxide / Fe3O4 composite sheet was added to 200 mL of ethanol, 1 g of silane coupling agent KH560 was added, heated to 40 ° C, stirred for 2 h, filtered, washed, and dried to obtain a modified composite sheet;

[0039] S3. Sol-gel reaction: 10 g of the modified composite sheet was added to 200 mL of water, the pH value of the solution was adjusted to 10, heated to 60 ° C, reacted for 7 h, filtered, washed, and dried to obtain a composite sheet;

[0040] S4 anionic surfactant treatment: 12g of the composite sheet was added to 200mL of water, 2g of sodium dodecylbenzene sulfonate was added, the reaction was stirred for 0.5h, filtered, washed, and dried to obtain a treated composite sheet;

[0041] S5. Reduction: The treated composite sheet was reduced with hydrazine hydrate vapor for 10 h to obtain a reduced composite sheet;

[0042] S6. Preparation of graphene-modified coating: 2 g of reduced composite sheet, 100 g of epoxy resin E-44, and 15 g of diethylenetriamine were stirred and mixed for 20 min to obtain a graphene-modified coating;

[0043] S7. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: evenly apply the graphene-modified coating on the tape, heat it to 50°C, and cure it for 4 hours to obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0044] Example 2

[0045] This embodiment provides a method for preparing a graphene-modified coating anti-corrosion solvent-free prefabricated composite adhesive tape, comprising the following steps:

[0046] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion under ice-water bath conditions, stirred and mixed for 15 min, the pH value of the solution was adjusted to 10, spray dried, and solid ball milled for 3 h to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0047] The spray drying conditions are as follows: the air inlet temperature is 120°C, the air outlet temperature is 50°C, and the evaporated water volume is 2700 mL / h;

[0048] S2. Preparation of modified composite sheet: 10 g of wrinkled graphene oxide / Fe3O4 composite sheet was added to 200 mL of ethanol, 2 g of silane coupling agent KH560 was added, heated to 50 ° C, stirred for 3 h, filtered, washed, and dried to obtain a modified composite sheet;

[0049] S3. Sol-gel reaction: 10 g of the modified composite sheet was added to 200 mL of water, the pH value of the solution was adjusted to 11, heated to 70 ° C, reacted for 10 h, filtered, washed, and dried to obtain a composite sheet;

[0050] S4 anionic surfactant treatment: 15g composite sheet was added to 200mL of water, 4g of sodium tetradecylbenzene sulfonate was added, the reaction was stirred for 1h, filtered, washed and dried to obtain a treated composite sheet;

[0051] S5. Reduction: The treated composite sheet was reduced with hydrazine hydrate vapor for 12 h to obtain a reduced composite sheet;

[0052] S6. Preparation of graphene-modified coating: 4 g of reduced composite sheet, 100 g of epoxy resin F-51, and 20 g of hexamethylenediamine were stirred and mixed for 20 min to obtain a graphene-modified coating;

[0053] S7. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: The graphene-modified coating is evenly coated on the tape, heated to 60°C, and cured for 2 hours to obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0054] Example 3

[0055] This embodiment provides a method for preparing a graphene-modified coating anti-corrosion solvent-free prefabricated composite adhesive tape, comprising the following steps:

[0056] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion under ice-water bath conditions, stirred and mixed for 15 min, the pH value of the solution was adjusted to 9.5, spray dried, and solid ball milled for 2 h to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0057] The spray drying conditions are as follows: the inlet air temperature is 110°C, the outlet air temperature is 40°C, and the evaporated water volume is 2550 mL / h;

[0058] S2. Preparation of modified composite sheet: 10 g of wrinkled graphene oxide / Fe3O4 composite sheet was added to 200 mL of ethanol, 1.5 g of silane coupling agent KH560 was added, heated to 45 ° C, stirred for 2.5 h, filtered, washed, and dried to obtain a modified composite sheet;

[0059] S3. Sol-gel reaction: 10 g of the modified composite sheet was added to 200 mL of water, the pH value of the solution was adjusted to 10.5, heated to 65 ° C, reacted for 8.5 h, filtered, washed, and dried to obtain a composite sheet;

[0060] S4 anionic surfactant treatment: 13.5g composite sheet was added to 200mL water, 3g of sodium tetradecylbenzene sulfonate was added, the reaction was stirred for 1h, filtered, washed and dried to obtain a treated composite sheet;

[0061] S5. Reduction: The treated composite sheet was reduced with hydrazine hydrate vapor for 11 hours to obtain a reduced composite sheet;

[0062] S6. Preparation of graphene-modified coating: 3 g of reduced composite sheet, 100 g of epoxy resin E-51, and 17 g of triethylenetetramine were stirred and mixed for 20 min to obtain a graphene-modified coating;

[0063] S7. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: The graphene-modified coating is evenly coated on the tape, heated to 55°C, and cured for 3 hours to obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0064] Comparative Example 1

[0065] Compared with Example 3, the difference is that ferric chloride and ferrous chloride are not added in step S1.

[0066] The details are as follows:

[0067] S1. Preparation of wrinkled graphene oxide sheets: 100 g of graphene oxide aqueous dispersion was spray dried and solid ball milled for 2 h to obtain wrinkled graphene oxide sheets;

[0068] The spray drying conditions are as follows: an inlet air temperature of 110° C., an outlet air temperature of 40° C., and an evaporation water volume of 2550 mL / h.

[0069] Comparative Example 2

[0070] Compared with Example 3, the difference is that the spray drying in step S1 adopts ordinary drying.

[0071] The details are as follows:

[0072] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheets: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion in an ice-water bath, and the mixture was stirred for 15 min. The pH value of the solution was adjusted to 9.5, and the mixture was dried at 105°C for 4 h and solid ball-milled for 2 h to obtain wrinkled graphene oxide / Fe3O4 composite sheets.

[0073] Comparative Example 3

[0074] Compared with Example 3, the difference is that steps S2 and S3 are not performed.

[0075] The details are as follows:

[0076] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion under ice-water bath conditions, stirred and mixed for 15 min, the pH value of the solution was adjusted to 9.5, spray dried, and solid ball milled for 2 h to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0077] The spray drying conditions are as follows: the inlet air temperature is 110°C, the outlet air temperature is 40°C, and the evaporated water volume is 2550 mL / h;

[0078] S2. Treatment with anionic surfactant: 13.5 g of wrinkled graphene oxide / Fe3O4 composite sheet was added to 200 mL of water, 3 g of sodium tetradecylbenzene sulfonate was added, the reaction was stirred for 1 h, filtered, washed, and dried to obtain a treated composite sheet;

[0079] S3 reduction: The treated composite sheet was reduced by hydrazine hydrate vapor for 11h to obtain a reduced composite sheet;

[0080] S4. Preparation of graphene-modified coating: 3 g of reduced composite sheet, 100 g of epoxy resin E-51, and 17 g of triethylenetetramine were stirred and mixed for 20 min to obtain a graphene-modified coating;

[0081] S5. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: The graphene-modified coating is evenly coated on the tape, heated to 55°C, and cured for 3 hours to obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0082] Comparative Example 4

[0083] Compared with Example 3, the difference is that step S4 is not performed.

[0084] The details are as follows:

[0085] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion under ice-water bath conditions, stirred and mixed for 15 min, the pH value of the solution was adjusted to 9.5, spray dried, and solid ball milled for 2 h to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0086] The spray drying conditions are as follows: the inlet air temperature is 110°C, the outlet air temperature is 40°C, and the evaporated water volume is 2550 mL / h;

[0087] S2. Preparation of modified composite sheet: 10 g of wrinkled graphene oxide / Fe3O4 composite sheet was added to 200 mL of ethanol, 1.5 g of silane coupling agent KH560 was added, heated to 45 ° C, stirred for 2.5 h, filtered, washed, and dried to obtain a modified composite sheet;

[0088] S3. Sol-gel reaction: 10 g of the modified composite sheet was added to 200 mL of water, the pH value of the solution was adjusted to 10.5, heated to 65 ° C, reacted for 8.5 h, filtered, washed, and dried to obtain a composite sheet;

[0089] S4 reduction: the composite sheet was reduced by hydrazine hydrate vapor for 11h to obtain a reduced composite sheet;

[0090] S5. Preparation of graphene-modified coating: 3 g of reduced composite sheet, 100 g of epoxy resin E-51, and 17 g of triethylenetetramine were stirred and mixed for 20 min to obtain a graphene-modified coating;

[0091] S6. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: The graphene-modified coating is evenly coated on the tape, heated to 55°C, and cured for 3 hours to obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0092] Comparative Example 5

[0093] Compared with Embodiment 3, the difference is that step S5 is not performed.

[0094] The details are as follows:

[0095] S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 100 g of graphene oxide aqueous dispersion under ice-water bath conditions, stirred and mixed for 15 min, the pH value of the solution was adjusted to 9.5, spray dried, and solid ball milled for 2 h to obtain a wrinkled graphene oxide / Fe3O4 composite sheet;

[0096] The spray drying conditions are as follows: the inlet air temperature is 110°C, the outlet air temperature is 40°C, and the evaporated water volume is 2550 mL / h;

[0097] S2. Preparation of modified composite sheet: 10 g of wrinkled graphene oxide / Fe3O4 composite sheet was added to 200 mL of ethanol, 1.5 g of silane coupling agent KH560 was added, heated to 45 ° C, stirred for 2.5 h, filtered, washed, and dried to obtain a modified composite sheet;

[0098] S3. Sol-gel reaction: 10 g of the modified composite sheet was added to 200 mL of water, the pH value of the solution was adjusted to 10.5, heated to 65 ° C, reacted for 8.5 h, filtered, washed, and dried to obtain a composite sheet;

[0099] S4 anionic surfactant treatment: 13.5g composite sheet was added to 200mL water, 3g of sodium tetradecylbenzene sulfonate was added, the reaction was stirred for 1h, filtered, washed and dried to obtain a treated composite sheet;

[0100] S5. Preparation of graphene-modified coating: 3 g of the treated composite sheet, 100 g of epoxy resin E-51, and 17 g of triethylenetetramine were stirred and mixed for 20 min to obtain a graphene-modified coating;

[0101] S6. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: The graphene-modified coating is evenly coated on the tape, heated to 55°C, and cured for 3 hours to obtain the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

[0102] Test Example 1

[0103] The coating performance of the graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape prepared in Examples 1-3 and Comparative Examples 1-5 was tested, and the results are shown in Table 1.

[0104] Test the coating flexibility according to GB / T1731-2020;

[0105] Test coating adhesion according to GB / T1720-2020;

[0106] Test the coating's salt spray resistance according to GB / T1771-2007;

[0107] Test the coating wear resistance according to GB / T1768-2006 (750g, 500r);

[0108] Impact resistance test according to GB / T1732-2020;

[0109] Test the water vapor permeability of the coating according to GB / T1037-2021;

[0110] The cathodic disbonding resistance of the coating was tested according to GB / T7790-2008 [1.5V, (65±2)℃].

[0111] Table 1

[0112]

[0113] It can be seen from the above table that the products prepared in Examples 1-3 of the present invention have good flexibility, high adhesion, good salt spray resistance, corrosion resistance, wear resistance, impact resistance, and cathode stripping resistance, and the coating has low water vapor permeability.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape, characterized in that: The graphene oxide, ferric chloride and ferrous chloride are uniformly mixed, spray-dried, and then modified by a silane coupling agent KH560, subjected to a sol-gel reaction, treated with an anionic surfactant, reduced by hydrazine hydrate vapor, and uniformly mixed with an epoxy resin and a curing agent to obtain a graphene-modified coating, which is uniformly coated on a rubber tape to obtain a graphene-modified coating anti-corrosion solvent-free prefabricated composite rubber tape; The method for preparing the graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape comprises the following steps: S1. Preparation of wrinkled graphene oxide / Fe3O4 composite sheet: adding ferric chloride and ferrous chloride to a graphene oxide aqueous dispersion under ice-water bath conditions, stirring and mixing, adjusting the pH value of the solution, spray drying, and solid ball milling to obtain a wrinkled graphene oxide / Fe3O4 composite sheet; the concentration of the graphene oxide aqueous dispersion is 0.5-1 mg / mL, the mass ratio of the graphene oxide aqueous dispersion, ferric chloride and ferrous chloride is 100:3.24:1.26, the pH value of the solution is adjusted to 9-10, the spray drying conditions are as follows: the inlet air temperature is 95-120°C, the outlet air temperature is 30-50°C, the evaporated water amount is 2400-2700 mL / h, and the ball milling time is 1-3h; S2. Preparation of modified composite sheet: adding the wrinkled graphene oxide / Fe3O4 composite sheet to ethanol, adding the silane coupling agent KH560, heating and stirring the reaction, filtering, washing, and drying to obtain a modified composite sheet; S3. Sol-gel reaction: adding the modified composite sheet to water, adjusting the pH value of the solution, heating the reaction, filtering, washing, and drying to obtain a composite sheet; S4 anionic surfactant treatment: the composite sheet was added to water, an anionic surfactant was added, the reaction was stirred, filtered, washed, and dried to obtain a treated composite sheet; S5 reduction: the treated composite sheet was reduced by hydrazine hydrate vapor to obtain a reduced composite sheet; S6. Preparation of graphene-modified coating: The reduced composite sheet, epoxy resin, and curing agent are uniformly mixed to obtain a graphene-modified coating; S7. Preparation of graphene-modified coating anti-corrosion solvent-free prefabricated composite tape: evenly coating the graphene-modified coating on the tape, heating and curing, and obtaining the graphene-modified coating anti-corrosion solvent-free prefabricated composite tape.

2. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the wrinkled graphene oxide / Fe3O4 composite sheet and the silane coupling agent KH560 is 10:1-2, the temperature of the heating and stirring reaction is 40-50°C, and the time is 2-3h; in step S3, the pH value of the solution is adjusted to 10-11, the temperature of the heating reaction is 60-70°C, and the time is 7-10h.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the composite sheet and the anionic surfactant in step S4 is 12-15:2-4, and the anionic surfactant is selected from at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium tetradecyl sulfonate, sodium tetradecylbenzene sulfonate, sodium tetradecyl sulfate, sodium hexadecyl sulfonate, and sodium octadecyl sulfonate.

4. The preparation method according to claim 1, characterized in that: The reduction time in step S5 is 10-12 hours.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the reduced composite sheet, epoxy resin and curing agent in step S6 is 2-4:100:15-20, the curing agent is selected from at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride and phthalic anhydride, and the epoxy resin is selected from at least one of E-51, E-44 and F-51.

6. The preparation method according to claim 1, characterized in that: The coating amount in step S7 is 300-400 g / m 2 The heating curing temperature is 50-60°C and the time is 2-4h.

7. A graphene-modified coating anti-corrosion solvent-free prefabricated composite tape prepared by the preparation method according to any one of claims 1 to 6.

8. An application of the graphene modified coating anti-corrosion solvent-free prefabricated composite adhesive tape as claimed in claim 7 in marine corrosion protection.

Citation Information

Patent Citations

  • High-strength electromagnetic-shielding heat-conducting PBT / PET nanocomposite material and preparation method thereof

    CN111925630A

  • Preparation method of epoxy resin / GO super-hydrophobic anticorrosive coating

    CN112409884A

  • Graphene modified anti-corrosion coating as well as preparation method and application thereof

    CN115181478A